STRATEGI MANAJEMEN PROGRAM EKSTRAKURIKULER DALAM OPTIMALISASI KEGIATAN NON-AKADEMIK SISWA DI SEKOLAH DASAR ISLAM TERPADU (SDIT) AL IBROHIMI MANYAR - Fahriyah Nela Rizka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the management strategies of extracurricular programs in optimizing students’ non-academic activities at SDIT Al-Ibrohimi Manyar. The research employed a descriptive qualitative approach with data collected through interviews, observation, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing verified continuously. The findings reveal that the management of extracurricular programs is implemented systematically through the core management functions: planning, organizing, actuating, controlling, and evaluating (POACE). Each function operates in an integrated manner, emphasizing the active involvement of teachers, coaches, and students. The main supporting factors include high student enthusiasm, professional coaching, and strong institutional support, while minor technical barriers are addressed through periodic evaluations. These strategies effectively enhance the quality of students’ non-academic activities, both in terms of achievement and the development of discipline, responsibility, and sportsmanship. The study highlights that the effectiveness of extracurricular management depends not only on efficient organizational structures but also on the consistency of sustainable coaching processes. The findings provide implications for developing Islamic education management models that emphasize holistic growth in students’ potential and character.